KONSEP PENERAPAN AREA TRAFFIC CONTROL SYSTEM (ATCS) UNTUK KABUPATEN KUBU RAYA - Zaki, Sheva Naufal; Sutandi, Anastasia Caroline (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2023)
Developments in urban planning and infrastructure development are still ongoing and being improved, which makes it challenging to handle transportation problems optimally. The transportation problem currently being faced is traffic jams. This study proposes implementing an Area Traffic Control System (ATCS) to overcome transportation problems at signalized intersections in Kubu Raya Regency. ATCS was implemented at Simpang 4 Major Alianyang-Adi Sucipto and Simpang 4 Major Alianyang-Raya Kapur Village. The method used to analyze intersection performance is MKJI 1997. The survey was carried out at peak hours on Wednesday and Saturday. Based on the results of the analysis using PTV VISSIM Software after implementing ATCS at the Major Alianyang-Adi Sucipto Intersection 4, it had a delay of 11,80 seconds with LOS B, and the Major Alianyang-Raya Intersection, Kapur Village, had a delay of 127,35 seconds with LOS F. ABSTRAK Perkembangan dalam pembangunan tata kota maupun infrastruktur masih terus berlangsung dan ditingkatkan, hal ini menyebabkan penanganan permasalahan transportasi sulit berjalan optimal. Permasalahan transportasi yang sedang dihadapi adalah kemacetan lalu lintas. Tujuan dari studi ini adalah memberikan konsep penerapan Area Traffic Control System (ATCS) untuk mengatasi permasalahan transportasi pada simpang bersinyal di Kabupaten Kubu Raya. Konsep penerapan ATCS dilakukan pada Simpang 4 Major Alianyang–Adi Sucipto dan Simpang 4 Major Alianyang–Raya Desa Kapur. Metode yang digunakan untuk menganalisis kinerja simpang adalah MKJI 1997. Survei dilakukan pada jam puncak hari Rabu dan Sabtu. Berdasarkan hasil analisis menggunakan Software PTV VISSIM setelah penerapan ATCS pada Simpang 4 Major Alianyang–Adi Sucipto memiliki tundaan 11,80 detik dengan LOS B dan Simpang 4 Major Alianyang–Raya Desa Kapur memiliki tundaan 127,35 detik dengan LOS F.